Genetically Engineered Viral Vectors and Organic‐Based Non‐Viral Nanocarriers for Drug Delivery Applications. Issue 20 (15th August 2022) - Hajebi, Sakineh; Yousefiasl, Satar; Rahimmanesh, Ilnaz; Dahim, Alireza; Ahmadi, Sepideh; Kadumudi, Firoz Babu; Rahgozar, Nikta; Amani, Sanaz; Kumar, Arun; Kamrani, Ehsan; Rabiee, Mohammad; Borzacchiello, Assunta; et al.
Abstract: Conventional drug delivery systems are challenged by concerns related to systemic toxicity, repetitive doses, drug concentrations fluctuation, and adverse effects. Various drug delivery systems are developed to overcome these limitations. Nanomaterials are employed in a variety of biomedical applications such as therapeutics delivery, cancer therapy, and tissue engineering. Physiochemical nanoparticle assembly techniques involve the application of solvents and potentially harmful chemicals, commonly at high temperatures. Genetically engineered organisms have the potential to be used as promising candidates for greener, efficient, and more adaptable platforms for the synthesis and assembly of nanomaterials. Genetically engineered carriers are precisely designed and constructed in shape and size, enabling precise control over drug attachment sites. The high accuracy of these novel advanced materials, biocompatibility, and stimuli‐responsiveness, elucidate their emerging application in controlled drug delivery. The current article represents the research progress in developing various genetically engineered carriers. Organic‐based nanoparticles including cellulose, collagen, silk‐like polymers, elastin‐like protein, silk‐elastin‐like protein, and inorganic‐based nanoparticles are discussed in detail. Afterward, viral‐based carriers are classified, and their potential for targeted therapeutics delivery is highlighted. Finally, the challenges and prospects of these delivery systems are concluded. Abstract : The organic and viral‐based genetically engineered carriers are classified, and their potential for targeted therapeutics delivery is highlighted. Also, the challenges and prospects of these delivery systems are concluded.